Bridging Growth And Sustainability: An Analytical Study Of Kiifb’s Role In Kerala’s Development Journey (International Journal of Environmental Sciences, 2024)
The Kerala Infrastructure Investment Fund Board (KIIFB) represents one of the most innovative fiscal instruments in Indian state-level infrastructure financing. This paper analyses KIIFB’s contribution to Kerala’s sustainable development during 2019–20 to 2023–24, focusing on its financial performance, project execution, and alignment with the Sustainable Development Goals (SDGs). Using secondary data from KIIFB Annual Reports and Kerala Economic Reviews, the study computes the compound annual growth rate (CAGR) in expenditure and examines the institution’s fiscal sustainability. Results show a CAGR of 32.1% in cumulative expenditure, indicating robust capital formation and efficient project delivery. However, increasing borrowings and a decline in new project approvals during 2023–24 reflect fiscal consolidation. The analysis concludes that KIIFB has successfully bridged the gap between growth and sustainability by integrating financial innovation with inclusive, environmentally responsible development in Kerala.